Differences in Euro-Area Household Finances and their Relevance for Monetary-Policy Transmission - Thomas Hintermaier; Winfried Koeniger (Institute of Labor Economics (IZA), 2019)
This paper quantifies the extent of heterogeneity in consumption responses to changes in real interest rates and house prices in the four largest economies in the euro area: France, Germany, Italy, and Spain. We first calibrate a life-cycle incomplete-markets model with a financial asset and housing to match the large heterogeneity of households asset portfolios, observed in the Household Finance and Consumption Survey (HFCS) for these countries. We then show that the heterogeneity in household finances implies that responses of consumption to changes in the real interest rate and in house prices differ substantially across countries, and within countries by household characteristics such as age, housing tenure, and asset positions. The different consumption responses quantified in this paper point towards important heterogeneity in monetary-policy transmission in the euro area.
Keywords: D14; D15; D31; E21; E43; G11; 330; european household portfolios; consumption; monetary policy transmission; international comparative finance; housing